Die Osterweiterung der Eurozone : Einige grundlegende Überlegungen zu Möglichkeiten und Risiken - Hanns-Dieter Jacobsen; Andrej Stuchlík (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
Once part of the European Union no 'opt-out' means, for CEE applicant countries, that they will have to become members of the Eurozone as soon as they fulfil the Maastricht criteria. However, compliance with the Stability and Growth Pact and aiming at nominal and real convergence imply efforts which are significantly higher than the 'simple' implementation of the acquis communautaire. Torn between completing their transformation process on the one hand and linking their economies as fast as possible to euroland on the other, most CEE countries face the risk of fixing their currency too eagerly, thus, being trapped to choose disinflation over growth. This paper presents the increased risk potential across the most important policy areas: capital markets, trade & FDI, labour markets, exchange rate policy, and monetary and fiscal policy. Moreover, a brief comparison of the Czech Republic and Poland reveals the need for further specific country analysis, since CEE countries' exposure to possible risks of the Eurozone enlargement vary significantly.
Keywords: F0; P2; E0; 330; EMU enlargement; monetary integration; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Osteuropa; EU-Staaten